1994
DOI: 10.1007/bf02167896
|View full text |Cite
|
Sign up to set email alerts
|

Family-expressed emotion, childhood-onset depression, and childhood-onset schizophrenia spectrum disorders: Is expressed emotion a nonspecific correlate of child psychopathology or a specific risk factor for depression?

Abstract: Expressed emotion (EE) was examined, using the brief Five Minute Speech Sample measure, in families of (1) children with depressive disorders, (2) children with schizophrenia spectrum disorders, and (3) normal controls screened for the absence of psychiatric disorder. Consistent with the hypothesis of some specificity in the association between EE and the form of child disorder, rates of EE were significantly higher among families of depressed children compared to families of normal controls and families of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
2
24

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 32 publications
9
102
2
24
Order By: Relevance
“…An accumulation of findings links the course of childhood disorder to characteristics of parent -child relations, specifically expressed emotion (EE). The extent of family criticism, hostility, and emotional overinvolvement predicted recovery rates one year after hospitalization in a sample of children hospitalized for depression irrespective of treatment method, ilness duration or comorbidity (Asarnow, Tompson, Hamilton, Goldstein, & Guthrie, 1994). Studies of children with physical disorders also imply that the course of these disorders is likely to be affected by parenting characteristics.…”
Section: The Current Case For Socializationmentioning
confidence: 98%
“…An accumulation of findings links the course of childhood disorder to characteristics of parent -child relations, specifically expressed emotion (EE). The extent of family criticism, hostility, and emotional overinvolvement predicted recovery rates one year after hospitalization in a sample of children hospitalized for depression irrespective of treatment method, ilness duration or comorbidity (Asarnow, Tompson, Hamilton, Goldstein, & Guthrie, 1994). Studies of children with physical disorders also imply that the course of these disorders is likely to be affected by parenting characteristics.…”
Section: The Current Case For Socializationmentioning
confidence: 98%
“…Several investigators have demonstrated that parent-child conflict is associated with the outcome of asthma in children [Hermanns et al, 1989;Schobinger et al, 1992;Strunk et al, 1985;Wamboldt et al, 1995]. Parental criticism and parent-child conflict have also been shown to be risk factors for depression and behavioral disorders in children [Asarnow et al, 1993[Asarnow et al, , 1994Vostanis et al, 1994]. Thus, parental criticism is associated with both asthma and depression in children and is a potential common environmental etiologic factor for both disorders.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, family conflict has been reported to be related to the onset, duration, and recurrence of pediatric and adult mood disorders. 1,2,45,46,56,57 Diminution of family conflict may be an important component for promoting recovery and preventing recurrences.…”
Section: Commentmentioning
confidence: 99%